(untitled) (Ameghiniana, 2023)
Pseudobeaconiidae is a South American endemic actinopterygian family recorded in the Middle–Late Triassic Cuyana and Ischigualasto-Villa Unión rift basins. This family has been studied for more than seven decades by several authors. In spite of that, the morphological information about their scales is not complete, especially the one related to micromorphology, which has remained unknown until now. The main goal of this contribution is to provide new macro- and micromorphological information of scales from new material of Pseudobeaconiidae, including a brief revision of the scales of the family based on our own observations from material collections. The new studied specimens were recovered from the center lake facies of the Santa Clara Abajo Formation with detailed stratigraphic control. The macromorphology of isolated scales confirms a peg-and-socket articulation in this newly studied material. New features described also include the squamation general pattern, including the scales of the lateral line, the ventral margin, that is characterized by round or angular scales, and the presence of ganoine ornamentations covering preanal and postanal scutes. Regarding micromorphology, paleohistology shows lepidosteoid- type ganoid scales and; also, possible transitional ganoid scales between lepidosteoid and palaeoniscoid-type. Detailed morphological studies on Triassic fish faunas are necessary to obtain clearer patterns that contribute to the understanding of the evolution of Actinopterygii from Gondwana.